Characteristic of Gross Pollutants and Evaluation of Gross Pollutant Traps (GPTs) in Perlis - Gressi Anak Rigum (Penerbit Universiti Malaysia Perlis, 2011)
Gross pollutant traps (GPTs) is a structural controlled device used as an early pretreatment for water especially in open channel. GPTs detained rubbish such as leaf, plastics, polystyrene, paper and sediment to reduce water pollution before it entering the main river. It is usually construct in an open channel with flow from several sources, and end to the outlet which is the river. The objective of this study is to characterize the pollutant traps in the GPTs accordingly and to monitor the water quality of water before and after the GPTs. From the observation and finding, an improved GPTs design is proposed. The method applied during this study are including weighing the rubbish, and sediment collected, water quality monitoring and laboratory analysis and designing a better GPTs system. There are five parameters involve in water quality sampling and analysis which are pH, DO, BOD, COD, SS and AN. This study is carried out at two point of GPTs in Kangar. Based on result obtain, it can be conclude that the pollutant traps can be characterize into five major group ; vegetative, plastics, paper, materials and sediment, with vegetative has the higher amount trapped in the GPTs system. Highest removal efficiency of SS in water quality in GPTs Point 2 show that the GPTs system can be an effective method to reduce water pollution if the maintenance of the GPTs system carried out properly. A Rubbish Trap is designed based on GPTs design criteria on MASMA for better performance.